POLA DISTRIBUSI POPULASI LUTUNG JAWA (Trachypitecus auraus E. Geoffroy Saint – Hilaire, 1812) DI CAGAR ALAM WATANGAN PUGER, KABUPATEN JEMBER - Muhammad Asyrofi; Hari Sulistiyowati; Retno Wimbaningrum (UIN Sunan Gunung Djati Bandung, 2021)
One of the primate species found in the Watangan Puger Nature Reserve is the Javan langur (Trachypitecus auraus). The IUCN Redlist classified this primate as vulnerable and it is included in CITES Appendix II. The aim of this study was to determine the distribution pattern of the Javan langur population in the Watangan Puger Nature Reserve. The data was collected from February to April 2021. A combination of concentrated method (Concentration Count) and ad libitum observation method was employed to obtain data. Analysis of the population distribution pattern was carried out using the Nearest Neighbor, while the population distribution was analyzed using the area of the outermost point of encounter. Both analyzes were performed using ArcGIS software version 10.1 and QGIS version 3.18. There are two distinct groups. In the first group, there were 17 individuals with a population density of 6.54 ind/km2, while in the second group were 9 individuals with a population density of 3.46 ind/km2. The distribution pattern of the population is classified as clustered in all groups with p-value and z-score of 0.000306 and-3.610344 for the first group and 0.000169 and-3.760636 for the second group respectively. The population distribution of Javan langurs in the Watangan Puger Nature Reserve covers about 43% of the total area.